Financial Inclusion, Shocks and Poverty: Evidence from the Expansion of Mobile Money in Tanzania - Olukorede Abiona; Martin Foureaux Koppensteiner (Institute of Labor Economics (IZA), 2018)
We estimate the effect of mobile money adoption on consumption smoothing, poverty and human capital investments in Tanzania. We exploit the rapid expansion of the mobile money agent network between 2010 and 2012 and combine this with idiosyncratic shocks from variation in rainfall over time and across space in an instrumented DiD methodology. We find that adopter households are able to smooth consumption during periods of shocks and maintain their investments in human capital. Results on time use of children and labor force participation complement the findings on the important role of mobile money for the intergenerational transmission of poverty.
Keywords: G23; H31; I31; I32; 330; mobile money; household shocks; rainfall; poverty; human capital accumulation; Tanzania